Biologia populacional de Emerita brasiliensis Schmitt (Crustacea, Hippidae) na Praia Vermelha do Norte, Ubatuba (São Paulo, Brasil) - Nakagaki, Jelly Makoto; Pinheiro, Marcelo Antonio Amaro [UNESP] (Sociedade Brasileira de Zoologia, 1999)
Emerita brasiliensis Schmitt, 1935 is a common mole crab called tatuíra in Brazil, with distribution from Espírito-Santo State (Brazil) to Buenos Aires Province (Argentina). Specimens were collected bimonthly from May/1992 through March/1993 with 4mm siffers mesh, in the intertidal region at Vermelha do Norte Beach, Ubatuba, São Paulo, Brazil. The animals were sexed and measured with a precision caliper of 0.1 mm (Cl = carapace length). Males presented cl amplitude from 3.4-17.3mm (13.2±2.1mm), and females from 13.8-26.3mm (20.5±1.8mm), showing a well-defined sexual dimorfism for this variable. The population presented a smaller incidence of males in relation to females (0.54:1.00), however in May/1992 an inverse pattern occurred (1.84:1.00). Ovigerous females were present in all samples with exception of May and September/1992 with greater frequencies in July/1992 and January/1993. It is probable that female maturity occurs is reached with 17mm CL, the smallest size in wich ovigerous females were found.
Population biology of Emerita brasiliensis Schmitt (Crustacea, Hippidae) in Vermelha do Norte beach, Ubatuba (São Paulo, Brazil)
Keywords: Hippidae; Emerita brasiliensis; population structure; sex-ratio